PENGARUH CURRENT RATIO (CR) DAN NET PROFIT MARGIN (NPM) TERHADAP RETURN ON ASSETS (ROA) PADA PT ANEKA TAMBANG, TBK TAHUN 2017-2022 - Zeze Zakaria Hamzah; Larasati; Muchammad Hamdani; Muhlis (Economicus, 2024)
This study is intended to determine the Effect of Current Ratio (CR) and Net Profit Margin (NPM) on Return on Assets (ROA) at PT Aneka Tambang, Tbk on financial statements in 2017-2022 and become one of the references regarding research on the analysis of financial statements in company. This research uses quantitative methods with classical assumption test techniques, multiple linear regression test, hypothesis test and determination coefficient test in IBM SPSS 22 statistical applications. The results in the classical assumption test, this study was found to have normal distribution values, did not experience heterochedascity, was not exposed to multico problems, and there was no autocorrelation. The linear regression test shows that the Current Ratio has an inversely proportional influence on the Return on Assets because it shows a positif value 0.010 while the Net Profit Margin has a direct influence on the Return on Assets because it shows a positive coefficient value 0,469. The results of the test concluded that the Current Ratio partially did not have a positive and significant effect on the Return on Assets, and the Net Profit Margin partially had a positive and significant effect on the Return on Assets. Meanwhile, simultaneously, Current Ratio and Net Profit Margin have a positive and significant effect on Return on Assets with a value of 73,1%.